[2]Pseudorotaxanes Based on Naphtho‐21‐crown‐7 and Secondary Dialkylammonium Salts: Remarkably Improved Association Constants Among Four Threaded Structures. Issue 4 (22nd April 2014) - Zhou, Qizhong; Luo, Yan; Jiang, Huajiang; Ye, Yuyuan; Zhang, Quan; Dai, Guoliang; Chen, Rener
Abstract This research article is focused on the recognition interaction of a new host naphtho‐21‐crown‐7 and four secondary dialkylammonium salts. In acetone, they can form 1:1 host‐guest complexes which belong to slow‐exchange systems. We also found the differences of binding affinity and binding selectivity between the host and its complementary guest moieties, which could be ascribed to the aromatic π‐π stacking effect and the acidity increase of N‐methylene and ammonium hydrogens due to the increasing electron withdrawing ability from butyl to methoxyphenyl to phenyl to p‐cyanophenyl substituents in the recognition motif.